Disruptive technologies in the supply chain and logistics: a systematic review - Tinoco-Plasencia, Christian Jairo (2024)
The purpose of the research was to offer a comprehensive analysis of disruptive technologies in supply chain and logistics. The study was carried out through a documentary and bibliographic approach, using a systematic review as a methodology. The PRISMA diagram was used to select the sample, composed of articles indexed in the Scopus database. Specific inclusion criteria were applied, selecting relevant articles published between 2020 and 2024 in any language and using any methodology, with open access. Those that only provided abstracts, duplicates, or were not aligned with the research objective were excluded. After this process, 25 publications were selected for analysis. A wide variety of innovative technologies applied in the field of supply and logistics management were identified. Evidence was found to suggest that the implementation of these technologies can considerably improve operational efficiency, reduce costs and increase the competitiveness of companies in the market.